PROFIL WANITA PENYALAHGUNA NARKOBA DI LEMBAGA PEMASYARAKATAN KELAS II B ANAK PEKANBARU - Kurnia Fajar Mulia; Swis Tantoro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Drug abuse is a crime, because it will give bad impact for people around the abuser her self, drug abuse is generally done by men, but as the growth of era, women did not escape the threat of drugs. Drug abuse among women is one case that has increased in recent years, especially in Pekanbaru. In institution of class II B for children Pekanbaru drug abuse conducted by women is the most cases compared to other criminal cases that is as much as 167 inmates at the end of 2016. This study is to find out what the characteristics of the perpetrators of drug abusers from the first story begins to use, the type of drugs that is consume up to the chronology of arrest and what factors that cause a drug abuse. The theory that is used is the theory of deviance and social action. Technique of sampling that is used in this research is purposive informant in selective according to criteria, informant amounted of 7 person, that is 5 main informant of woman’s drug abuse and 2 person as a key informant, 1 from BNN riau province and 1 person investigator from Polresta Drug Units . Method of data analysis is use a qualitative descriptive data retrieval use interview technique and documentation. The result of research explain that the background that cause woman abusing drugs interrelated. Both the background from within and from outside such as family disharmony to the most influential is the social environment.Keywords: Woman, Drug Abuse, Sosial Deviation